Pattern, management and outcome of acute intestinal obstruction at Chitwan medical college teaching hospital - Bhattarai, Abhishek; Devkota, Pragya; Shrestha, Anup; Chand, Manoj; Timalsina, Santosh; Tamrakar, Kishor Kumar; Neupane, Harish Chandra (Journal of Chitwan Medical College, 2022)
Background: Acute intestinal obstruction is one of the commonly encountered emergencies in surgical practice. Gynecological surgery, especially adnexal surgery and hysterectomy has a higher incidence of bowel obstruction as compared to bowel surgery. Conservative management can be done in patients with post-operative adhesive bowel obstruction if there is no evidence of ischemia, bowel necrosis, or perforation. Therefore, a correct diagnosis is essential for appropriate management. We conducted a study to evaluate the etiology, clinical presentation as well as management and outcome of patients presenting with Acute intestinal obstruction at our center. Methods: This was a retrospective study of all the patients with a diagnosis of Acute intestinal obstruction from January 2015 to December 2019. The diagnosis of Acute intestinal obstruction was made by a combination of clinical and radiological parameters. The data were analyzed using Statistical Package for Social Sciences (SPSS) for Windows version 16. The data were expressed in number and percentage. Results: During the study period, 178 patients were admitted with the diagnosis of Acute intestinal obstruction. Abdominal pain and vomiting were the main complaints seen in 98.3% (n=175) and 84.8% (n=151) respectively. Hernia (n=49, 27.5%) was the most common cause of acute intestinal obstruction in adults, and Intussusception (n=15, 8.4%) was the leading cause of Acute intestinal obstruction in a pediatric age group. Majority of the patients’ needs (n=148,83.1%) operative intervention to relieve the obstruction. The overall mortality rate was 6.7% (n=12). Conclusions: Hernia was the most common cause of Acute intestinal obstruction in adults while intussusception was the commonest in the pediatric age group.